Paradoks Opini Audit dan Akuntabilitas Substantif dalam Tata Kelola Keuangan Pemerintah Daerah: Analisis Kota Bandung Tahun 2022–2024 Berbasis Comprehensive Accountability Framework - Muhammad Abdillah Faqih Mardiansyah; Erwin Irawan; Kalvin Yulnex; Tita Nurjanah (Journal of Citizenship, 2026)
This study examines the gap between formal and substantive accountability in the financial management of the Bandung City Government during 2022–2024. Using a Comprehensive Accountability Framework (CAF), the study analyzes how improved audit opinions may coexist with persistent risks of irregularities. Data were collected through document analysis of audit reports issued by the Supreme Audit Agency, local government financial statements, inspectorate reports, and relevant regulations. The findings show that improved audit opinions reflect strengthened administrative accountability but have not been accompanied by enhanced substantive accountability, particularly in public procurement and asset management. This study concludes that favorable audit opinions do not necessarily indicate the actual quality of financial governance, reinforcing the audit opinion paradox in local government.